The structural and functional analysis of mycobacteria cysteine desulfurase-loaded encapsulin - Tang, Yanting; Liu, Yanyan; Zhang, Mingjing; Lan, Weiqi; Ma, Mengyuan; Chen, Cheng; Wu, Saibin; Chen, Rong; Yan, Yiran; Feng, Lu; Li, Ying; Guddat, Luke W.; et al. (Communications biology, 2024)
Encapsulin nanocompartments loaded with dedicated cargo proteins via unique targeting peptides, play a key role in stress resistance, iron storage and natural product biosynthesis. Mmp1 and cysteine desulfurase (Enc-CD) have been identified as the most abundant representatives of family 2 encapsulin systems. However, the molecular assembly, catalytic mechanism, and physiological functions of the Mmp1 encapsulin system have not been studied in detail. Here we isolate and characterize an Enc-CD-loaded Mmp1 encapsulin system from Mycobacterium smegmatis mc 2 155. The cryo-EM structure of the Mmp1 encapsulin and the crystal structure of the naked cargo Enc-CD have been determined. The structure shows that the Mmp1 protomer assembles two conformation models, the icosahedron ( T = 1) and homodecamer, with the resolution of 2.60 Å and 2.69 Å. The Enc-CD at 2.10 Å resolution is dimeric and loaded into the Mmp1 ( T = 1) encapsulin through the N-terminal long disordered region. Mmp1 encapsulin protects Enc-CD against oxidation as well as to maintain structural stability. These studies provide new insights into the mechanism by which Enc-CD-loaded encapsulin stores sulfur and provides a framework for discovery of new anti-mycobacterial therapeutics. Tang et al. present the isolation and characterization of an Mmp1 encapsulin system from Mycobacterium smegmatis , highlighting its structural and functional features. The study reveals the cryo-EM and crystal structures, offering insights into the role of Enc-CD-loaded encapsulin in sulfur storage, stress resistance, and potential therapeutic applications against mycobacterial infections.